Game-Based Learning: The Educational Board Game Trend - Nur Azwa Humaira’ Mohd Norazizi; Nurhidaya Mohamad Jan; Shafinah Kamarudin; Hatika Kaco; Fadzidah Mohd Idris; Engku Nor Hamidah Engku Abdul Rahman; Amelia Natasya Binti Abdul Wahab4; Siti Munirah Mohd (Kolej PERMATA Insan, 2024)
4th Insan Junior Researchers International Conference 2023 (iJURECON 2023) : "STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Nurhidaya Mohamad Jan, Nur Aisyah Mohamed, Nur Fatin Fathillah Mazlan 27-28 October 2023 Organized by : Kolej Permata Insan